2010
DOI: 10.1007/978-3-642-11808-1_14
|View full text |Cite
|
Sign up to set email alerts
|

Argumentation about Treatment Efficacy

Abstract: The volume and complexity of knowledge produced by medical research calls for the development of technology for automated management and analysis of such knowledge. In this paper, we identify scenarios where a researcher or a clinician may wish to use automated systems for analysing knowledge from clinical trials. For this, we propose a language for encoding, capturing and synthesising knowledge from clinical trials and a framework that allows the construction of arguments from such knowledge. We develop this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Moreover, it would be helpful to have a method for automatically analyzing and presenting the clinical trial results and the possible ways to aggregate those in an intuitive form, highlighting agreement and conflict present within the literature. As a first step to addressing these needs, our proposal in [3], [1], [2] presents a general framework for representing and synthesizing knowledge from clinical trials involving the same outcome indicator (e.g. overall survival, or disease-free survival).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it would be helpful to have a method for automatically analyzing and presenting the clinical trial results and the possible ways to aggregate those in an intuitive form, highlighting agreement and conflict present within the literature. As a first step to addressing these needs, our proposal in [3], [1], [2] presents a general framework for representing and synthesizing knowledge from clinical trials involving the same outcome indicator (e.g. overall survival, or disease-free survival).…”
Section: Introductionmentioning
confidence: 99%
“…In [59], rules were used to combine treatments for multimorbidity, and in [19] clinical guideline expressions were encoded in GELLO. Authors in [57] defined patterns of eligibility criteria for clinical trials that cover most criteria found in clinical guidelines and [40] proposed a language to capture and synthesize the knowledge generated in such trials. Knowledge in clinical guidelines were also represented in first order logic [74] or combined under a mathematical model, in order to deal with comorbidity [72].…”
Section: Knowledge Specificationmentioning
confidence: 99%
“…Our proposal in [9,8] aims to suggest such a method. The first part of our proposal is a language that can be used to encode the published results in a semantically appropriate way, and methods for constructing a knowledge base from the encoded results.…”
Section: Introductionmentioning
confidence: 99%